2021
DOI: 10.1002/cne.25108
|View full text |Cite
|
Sign up to set email alerts
|

Conservation and dimorphism in androgen receptor distribution in Alston's singing mouse ( Scotinomys teguina )

Abstract: Because of their roles in courtship and intrasexual competition, sexual displays are often sexually dimorphic, but we know little about the mechanisms that produce such dimorphism. Among mammals, one example is the vocalization of Alston's singing mouse (Scotinomys teguina), which consists of a series of rapidly repeated, frequency‐modulated notes. The rate and duration of songs is sexually dimorphic and androgen responsive. To understand the neuronal mechanisms underlying this sexual dimorphism, we map the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 129 publications
(194 reference statements)
0
7
0
Order By: Relevance
“…In another study (Zheng et al, 2021), we identify the presence of androgen receptors across this broad circuit, providing a potential mechanism for the androgen-dependence of Scotinomys song (Pasch et al, 2011). We have also found that body condition in general, and circulating leptin specifically, is associated with individual differences vocal effort.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…In another study (Zheng et al, 2021), we identify the presence of androgen receptors across this broad circuit, providing a potential mechanism for the androgen-dependence of Scotinomys song (Pasch et al, 2011). We have also found that body condition in general, and circulating leptin specifically, is associated with individual differences vocal effort.…”
Section: Discussionmentioning
confidence: 58%
“…Among singing mice, as in many other taxa, display effort is influenced by reproductive state and body condition (Burkhard et al., 2018; Giglio & Phelps, 2020; Pasch et al., 2011b). In another study (Zheng et al., 2021), we identify the presence of androgen receptors across this broad circuit, providing a potential mechanism for the androgen‐dependence of Scotinomys song (Pasch et al., 2011). We have also found that body condition in general, and circulating leptin specifically, is associated with individual differences vocal effort.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…More detailed studies explore the expression of these receptors in different subregions of the PAG. AR and ER, for example, can be found in the dorsal and lateral columns of PAG, as well as the ventral portions of the region ( Loyd and Murphy, 2008 ; Murphy et al, 1999 ; Zheng et al, 2021 ). Some of this work even pinpoints likely AR and ER expression to PAG neurons that project to medullary nuclei, which in turn innervate spinal motoneurons ( Loyd and Murphy, 2008 ).…”
Section: Pag Forms Part Of a Circuit Module That Is Hormonally Regula...mentioning
confidence: 99%